Reflections on my career in analytical chemistry and biochemistry - SWEELEY, Charles C. (The Japan Academy, 2010)
My career has been focused in two major areas, analytical chemistry and biochemistry of complex lipids and glycoconjugates. Included here are the pioneering work on the gas chromatography of long-chain sphingolipid bases, carbohydrates, steroids and urinary organic acids. Mass spectrometry was utilized extensively in structural studies of sphingolipids, fatty acids, carbohydrates, steroids, urinary organic acids, polyisoprenoid alcohols, and juvenile hormone. Computer systems were developed for the acquisition and analysis of mass spectra, and were used for development of automated metabolic profiling of complex mixtures of metabolites. Fabry’s disease was discovered to be a glycosphingolipidosis. Enzymes of lysosomal metabolism of glycosphingolipids were purified, characterized, and used in one of the first demonstrations of the feasibility of enzyme replacement therapy in a lysosomal storage disorder (Fabry’s disease). Extracellular sialidases were studied to evaluate the hypothesis that they might be involved in the regulation of membrane growth factor receptors. The enzyme for hematoside synthesis was purified and characterized.